1997
DOI: 10.1046/j.1365-2370.1997.d01-108.x
|View full text |Cite
|
Sign up to set email alerts
|

Hla‐dr4 Subtype and ‐b Alleles in Dqb1*0302‐positive Haplotypes Associated With Iddm

Abstract: We determined the distribution of DR4 subtypes in 309 DQB1*0302-positive haplotypes found in insulin-dependent diabetes mellitus (IDDM) patients and 70 control haplotypes present only in healthy family members. An increased frequency of DRB1*0401 allele (74.4% vs. 55.7%, P = 0.003) and a decrease of DRB1*0404 allele (23.6% vs. 40.0%, P = 0.0064) was revealed. A further analysis of extended haplotypes demonstrated strong linkages between various B alleles and DRB1*04 subtypes. HLA-B39 was more frequent in DRB1*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
3
21
1
Order By: Relevance
“…In the DR3/404-stratified group, we confirmed strong diabetes association of B39, previously shown by us (3,4), and of A24, shown by others (7,8). There was only one allele at each microsatellite locus associated with an increased risk for type 1 diabetes, and all of these alleles, as well as A24, were strongly associated with B39 ( Table 1).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In the DR3/404-stratified group, we confirmed strong diabetes association of B39, previously shown by us (3,4), and of A24, shown by others (7,8). There was only one allele at each microsatellite locus associated with an increased risk for type 1 diabetes, and all of these alleles, as well as A24, were strongly associated with B39 ( Table 1).…”
supporting
confidence: 88%
“…associated with a conspicuously high risk on this haplotype (3,4). At the same time, it was shown that B39 is in linkage disequilibrium with the HLA-A24 allele on the DR404 haplotype (4).…”
Section: S Nejentsev and Associatesmentioning
confidence: 99%
“…41 In addition, it is possible that the same single locus in the class II-centromeric class I region also explains the heterogeneity in risk reported for DQ8-DRB1*0404 haplotypes in Finland. 7,9 Zavattari et al 10 suggested that three markers, DMB, DOB and TNFc, were independently associated with T1D, but these data could be explained by a single extended susceptibility haplotype. Nonetheless, Sardinian haplotypes differ significantly centromeric of DQB1, and a third non-DQ/DR variant reducing the DQ2-DR3 haplotype susceptibility in this population is a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Although most A Ã 24 alleles do show a predisposing effect, a study of T1D in a Filipino population showed that A Ã 24:07, which differs from A Ã 24:02 by the substitution of Gln for His at position 70, is not predisposing for T1D . B Ã 39 alleles appear to be the most highly predisposing class I alleles, with the B Ã 39:06 allele most commonly associated with T1D (Ilonen et al 1992;Nejentsev et al 1997;Reijonen et al 1997;Valdes et al 2005;Noble et al 2010). B Ã 3906 increases T1D risk for moderate susceptibility haplotypes, such as DR1, DR8, and even DR16 (a type of DR2) haplotypes Baschal et al 2011).…”
Section: Hla Class Imentioning
confidence: 99%